Edukasi Obat dan Penanganan Kecemasan di Masa Pandemi Covid 19 - Muhammad Andi Setiawan; Guntur Satrio Purnomo; Dedy Setyawan; Dewi Sari Mulya (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this community service is to provide treatment for anxiety during the Covid-19 period and worries about drug use. This condition is based on the increasing number of corona cases in Palangkaraya, which has an impact on anxiety that will be even higher. If you let anxiety, it will have an impact on prolonged stress and can lead to personality disorders. Various efforts have been made to anticipate corona, one of which is by providing education and prevention of anxiety about the use of drugs but drugs also have an adverse effect, especially pregnant and lactating women. The method approach used in community service is educational and persuasive, namely this program has learning values (education) as well as an invitation for the community to improve the quality of community life, especially in the health sector in the form of theory and practice for ± 5 months (10 activities). The method used is descriptive and quantitative analysis. The socialization and mentoring activities of drug education and anxiety management in the PKK Palangkaraya City resulted in an in-depth understanding of drugs and also how to deal with anxiety that appears especially during the Covid 19 pandemic.[H1]  [H1]Abstrak sesuai